2019
DOI: 10.1055/s-0039-1681096
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Pain Management for Cesarean Delivery: A Double-Blinded, Placebo-Controlled, Randomized Clinical Trial

Abstract: Objective Our objective was to evaluate the efficacy of perioperative multimodal pain management in reducing opioid use after elective cesarean delivery (CD). Study Design A single-center, double-blinded, placebo-controlled randomized trial of women undergoing elective CD. Participants were allocated 1:1 to receive the multimodal protocol or matching placebos. The multimodal protocol consisted of a preoperative dose of intravenous acetaminophen, preincision injection of subcutaneous bupivacaine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This finding is similar to other studies that have evaluated the efficacy of ERAS after CD for postoperative pain control. 4 5 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is similar to other studies that have evaluated the efficacy of ERAS after CD for postoperative pain control. 4 5 15…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to other studies that have evaluated the efficacy of ERAS after CD for postoperative pain control. 4,5,15 Clinical Implications ERAS implementation was associated with significantly decreased racial and ethnic differences in POD1 and POD2 VAS pain scores with movement but not at rest after CD. Notably, our data show a trend toward higher total opioid use in NHB women compared with all other groups in both the pre-and post-ERAS timeframes although this difference did not meet statistical significance.…”
Section: Principal Findings Of the Studymentioning
confidence: 96%
“…Some investigators have shown that acetaminophen or NSAIDs could decrease the requirement of postoperative opioids, 17 while others were of the opposite view. 18,19 Transversus abdominis plane (TAP) blocks helped provide improved postoperative analgesia and reduce morphine consumption in patients who underwent CD under general anesthesia, 20 but not in those who received intrathecal morphine. 21 Compared to the standard analgesic regimen, TAP blocks do not have any effect in reducing the incidence or severity of chronic postsurgical pain after CD.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a multimodal postoperative pain management regimen alone, without other ERAS measures, can provide a meaningful change to current practice even in facilities with limited resources. Other studies such as the randomized control trial by Hadley et al 15 did not demonstrate a difference in opioid consumption. However, nonnarcotic pain medications such as acetaminophen and ibuprofen were not scheduled after surgery and were only administered as needed, which was a limitation recognized by the authors.…”
Section: Discussionmentioning
confidence: 85%
“…12 whereas others showing no difference. 11,15 While we plan to implement other portions of the ERAS for cesarean delivery guidelines in the future, we were able to demonstrate that a dramatic decrease in postoperative opioid use was possible with a change to a simple medication regimen alone.…”
Section: Figurementioning
confidence: 92%